CONSTRAINT FACTORS OF FOOD COMPETITIVENESS IN JAVA ISLAND: AHP APPROACH - Harini Harini; Yunastiti Purwaningsih; Malik Cahyadin; Emi Widiyanti (Journal of Applied Economics in Developing Countries, 2018)
This study aims to analyze the constraining factors of food competitiveness on the Java island, Indonesia. The data used are primary data with samples of 245 sellers. The sampling method used is purposive sampling. The data analysis method used is Analytical Hierarchy Process (AHP). The process of data analysis begins with identifying and calculating the weight of the perception of all the constraining factors of food competitiveness. At this stage, fifteen factors with the highest and lowest weight are obtained. They, respectively, are fluctuated purchase price of local food and the lack of IT facilities for the buyer to obtain food information. The next stage is the prioritization of the constraining factors of food competitiveness.  Based on AHP approach, there are eight factors constraining food competitiveness with the first and last priority, respectively are, the integration of the agricultural business upstream - downstream and food commodity prices.Keywords: Competitiveness, Food, AHP